Acute mountain sickness: pathophysiology and prevention - Moczydłowski, Paweł; Kuczapska, Karolina; Gliwa, Anna; Ryglewicz, Monika; Fabian, Dariusz; Leszczyńska-Knaga, Elżbieta; Jakubczyk, Natalia; Rutkowska-Kawalec, Weronika; Kurowski, Marek; Michalczuk, Karolina (Quality in Sport, 2025)
This review discusses the epidemiology, pathophysiology, prevention and treatment of acute mountain sickness (AMS). Key mechanisms including changes in blood-brain barrier permeability, activation of the renin-angiotensin-aldosterone system and the role of diuresis in the development of AMS are analysed. The effectiveness of various preventive strategies, such as acclimatisation and pharmacotherapy (acetazolamide, dexamethasone, ibuprofen), as well as alternative approaches, including the use of natural remedies such as Rhodiola roses, coca leaves and Ginkgo biloba, are discussed. The paper emphasises the importance of correct diagnosis and prompt action in the treatment of AMS, which is crucial in preventing complications. Material and methods Data bases such as Pubmed and GoogleScholar were used for research with the key words: acute mountain illness (AMS), acetazolamid, dexametazone, altitude, prevention, acclimatisation. Conclusions Acute altitude sickness is a challenge in terms of understanding pathophyslogy and effective treatment methods. The primary methods of preventing AMS are properly managed acclimatisation and the use of acetazolamide. Other pharmacological and natural measures require further research.